The impact of digital economy on green finance in China - He, Li; Malim, Nurhafiza Abdul Kader; Xuyang, Du (International Journal of Innovative Research and Scientific Studies, 2025)
In response to China’s dual carbon goals and the global imperative for sustainable development, this study investigates how the digital economy influences green finance (measured by carbon efficiency) across China’s provinces. While prior research acknowledges the promise of digital technologies in promoting low-carbon growth, few studies rigorously quantify their impact on green finance. To address this gap, this study utilizes a balanced panel dataset of 31 Chinese provinces from 2000 to 2020. A composite digital economy index is constructed using the entropy-weighted method, and green finance is measured using a carbon efficiency metric based on the DEA-SBM model. The relationship is evaluated through Tobit regression models, with a focus on regional heterogeneity. The findings reveal that the digital economy has a significantly positive effect on green finance at the national level and in eastern and western China, but no statistically significant relationship is found in central China. Additionally, GDP growth negatively affects green finance in all regions, reflecting a persistent carbon-intensive growth pattern. The effects of energy use and industrial structure vary by region, indicating persistent regional structural disparities. The results suggest that while digitalization can serve as a critical enabler of green finance in China, its benefits are unevenly realized across provinces. This study provides novel empirical evidence on the interactions between digital infrastructure and environmental finance, highlighting the need for region-specific policy responses. The findings underscore the potential of digital transformation to align environmental objectives with economic development and provide actionable insights for policymakers aiming to harmonize growth with ecological sustainability.